1956
DOI: 10.1139/v56-166
|View full text |Cite
|
Sign up to set email alerts
|

THE MICROPORE FLOW OF H2O AND D2O THROUGH ACTIVATED CARBON RODS

Abstract: The flow rates of water adsorbed on activated charcoal have been measured a t temperatures between -24°C. and f35"C. and compared with the flow rate of adsorbed D?O a t 25OC. In earlier papers a formula was presented which describes the ~nicropore flow rate of adsorbed water as a laminar flow of liquid adsorbate under a high pressure gradient due to surface forces. Our results confirm this picture. From our flow data the relative viscosity of adsorbates can be calculated. Above 0°C. the viscosity of the adsorb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

1962
1962
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…The location of these samples relative to the LMWL is characteristic of a nonequilibrium fractionation event, or, alternatively, may be due to mixing with an undefined source that has a strongly negative δ 18 O composition. Laboratory studies show that H 2 O flow rates are higher than D 2 O through micropores in carbon rods [ Huber et al ., ], and across a sulfanated polystyrene membrane [ Myagkov , ]. Additionally, fractionation due to filtration was measured as water passed through a 35% porosity montmorillonite disc [ Coplen and Hanshaw , ].…”
Section: Discussionmentioning
confidence: 99%
“…The location of these samples relative to the LMWL is characteristic of a nonequilibrium fractionation event, or, alternatively, may be due to mixing with an undefined source that has a strongly negative δ 18 O composition. Laboratory studies show that H 2 O flow rates are higher than D 2 O through micropores in carbon rods [ Huber et al ., ], and across a sulfanated polystyrene membrane [ Myagkov , ]. Additionally, fractionation due to filtration was measured as water passed through a 35% porosity montmorillonite disc [ Coplen and Hanshaw , ].…”
Section: Discussionmentioning
confidence: 99%
“…Transport of gases or vapors through porous materials is governed by different mechanisms depending on the size of the pores. In macroporous materials ( d p > 50 nm), viscous flow and Knudsen diffusion occur in the absence of gas−solid interaction other than reflection of the gas molecules at the pore wall. , Whereas in mesoporous materials (2 nm < d p < 50 nm), the transport varies from diffusive in the dilute monolayer region with gas molecules experiencing an interaction with the pore wall , to hydrodynamic when the adsorbate is in the form of multimolecular layers or liquid condensate. In microporous materials ( d p < 2 nm), it was shown that the size of the gas molecules and the specific molecule−wall interactions could lead to distinct differences in potential energy barriers and therefore transport rate. However, the transport mechanism through amorphous microporous materials is still under discussion. The derivation of a multilayer diffusion equation is carried out below to interpret the transport mechanism of gases or vapors through microporous materials, assuming that the BET n-layer adsorption takes place and that the transport of the adsorbed molecules is controlled by the activated diffusion mechanism …”
Section: Multilayer Diffusion Equationmentioning
confidence: 99%
“…This is acceptable, with the proviso that κ c in eq 7 does not vary significantly with v s . On this basis, a simple result, equivalent to 9 and subject to the restriction that v s → 1, was derived by Flood et al In spite of this severe restriction, eq 9 is at the basis of the following formulation of J s in the multilayer adsorption region: ,,, Equation 10 follows from eqs 7 and 9 and states that the flux produced by the real liquid sorbate (which is inhomogeneously distributed in the pore space) is equivalent to the flux which would be observed (under otherwise identical conditions) if the pore space was saturated with a (imaginary) fluid of the same viscosity as the real sorbate but of higher molar volume V s = V L / v s and subject to a correspondingly lower hydrodynamic pressure gradient, as dictated 4 by the thermodynamic relation V s d p s = V L d p L .…”
Section: Formulation Of Surface Transportmentioning
confidence: 99%